Carpal tunnel syndrome caused by tophi in the superficial flexor tendon: a case report - Hao, Haihu; Kong, Weijie; Li, Han (Frontiers in Surgery, 2023)
Carpal tunnel syndrome caused by tophi in the superficial flexor tendon—a case reportCarpal tunnel syndrome(CTS) is the most common disease among peripheral nerve entrapment diseases. CTS is often caused by the hyperplasia of the transverse carpal ligament and edema of tissue in the carpal tunnel, resulting in compression of the median nerve. Specific manifestations of CTS include numbness, loss of skin sensation in the palm and three and a half fingers on the radial side, and decreased muscle strength, however, CTS caused by wrist tophi is very rare. To our knowledge, CTS with median nerve compression caused by tophi in the superficial flexor tendon of the index finger of the wrist has not been reported before. Here, we will report a case of CTS caused by tophi in the wrist in a 37-year-old patient with no history of gout. Conclusion: CTS caused by tophi is uncommon, but if the patient has high uric acid, CTS may be due to tophi.